The HOX code of human adult fibroblasts reflects their ectomesenchymal or mesodermal origin - Pfeiferová, Lucie; Španko, Michal; Šáchová, Jana; Hradilová, Miluše; Pienta, Kenneth J; Valach, Jaroslav; Machoň, Vladimír; Výmolová, Barbora; Šedo, Aleksi; Bušek, Petr; Szabo, Pavol; Lacina, Lukáš; et al. (Histochemistry and cell biology, 2025)
Fibroblasts, the most abundant cell type in the human body, play crucial roles in biological processes such as inflammation and cancer progression. They originate from the mesoderm or neural-crest-derived ectomesenchyme. Ectomesenchyme-derived fibroblasts contribute to facial formation and do not express HOX genes during development. The expression and role of the HOX genes in adult fibroblasts is not known. We investigated whether the developmental pattern persists into adulthood and under pathological conditions, such as cancer. We collected adult fibroblasts of ectomesenchymal and mesodermal origins from distinct body parts. The isolated fibroblasts were characterised by immunocytochemistry, and their transcriptome was analysed by whole genome profiling. Significant differences were observed between normal fibroblasts from the face (ectomesenchyme) and upper limb (mesoderm), particularly in genes associated with limb development, including HOX genes, e.g., HOXA9 and HOXD9. Notably, the pattern of HOX gene expression remained consistent postnatally, even in fibroblasts from pathological tissues, including inflammatory states and cancer-associated fibroblasts from primary and metastatic tumours. Therefore, the distinctive HOX gene expression pattern can serve as an indicator of the topological origin of fibroblasts. The influence of cell position and HOX gene expression in fibroblasts on disease progression warrants further investigation.
Keywords: Fibroblasts; Expression pattern; homeoboxové geny; kultivované buňky; Adult; mezoderm; Cells, Cultured; fibroblasty; Homeodomain Proteins; Mesoderm; dospělí; lidé; Genes, Homeobox; Ectomesenchyme; Homeobox genes; homeodoménové proteiny; Humans; Cancer-associated fibroblasts